Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Teknik Instalasi Penerangan Listrik Rumah Sederhana Di SMKN 1 Darul Kamal - Akbarul Kautsar; Marzuki Marzuki; Sadrina Sadrina (PTE FTK UIN Ar-Raniry, 2018)
This research is motivated by the low learning outcomes of students in subjects Simple home electric lighting installation techniques, this is because the learning process is still teacher-centered. This study aims to reveal differences in student learning outcomes between jigsaw cooperative learning models with conventional models in subjects of simple home electric lighting installation techniques at SMK 1 Darul Kamal and to improve student learning outcomes. The research method used was Pre-Experiment with the research subjects of the 11th grade students of TITL SMKN 1 Darul Kamal consisting of 1 class, students were divided into 2 groups, namely the experimental group and the control group. From the results of data analysis based on the results of the t-test shows that Ho is rejected based on the significance value <α = 5% or 0.05, in the column t-test for equality of means we see in the column